2009
DOI: 10.1016/s2255-4971(15)30266-4
|View full text |Cite
|
Sign up to set email alerts
|

Osteosynthesis With Intramedullary Nails in Children

Abstract: The authors present a comprehensive review of the literature emphasizing the use of flexible intramedullary nails in the treatment of fractures in children, focusing the treatment of femoral shaft and forearm fractures and emphasizing the importance of the non-surgical approach. Children's age and weight threshold are not well defined for the use of the method. The removal of implants is a controversial matter in the literature, with a trend towards keeping the implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
6
0
2
Order By: Relevance
“…1 Although fractures of the bones of the forearm are successfully treated conservatively, outcomes remain variable, and, subsequently, some cases may require additional fracture manipulation or formal surgical intervention due to residual angulations. 2 3 4 5 6 Previous studies have shown that the failure of nonoperative treatment of midshaft fractures in pediatric populations ranges between 39 and 64%. 3 Alternatives include closed remanipulation and casting, pins and plaster, closed or mini-open reduction, intramedullary (IM) nailing, and open reduction and internal fixation (ORIF) with plates and screws.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although fractures of the bones of the forearm are successfully treated conservatively, outcomes remain variable, and, subsequently, some cases may require additional fracture manipulation or formal surgical intervention due to residual angulations. 2 3 4 5 6 Previous studies have shown that the failure of nonoperative treatment of midshaft fractures in pediatric populations ranges between 39 and 64%. 3 Alternatives include closed remanipulation and casting, pins and plaster, closed or mini-open reduction, intramedullary (IM) nailing, and open reduction and internal fixation (ORIF) with plates and screws.…”
Section: Introductionmentioning
confidence: 99%
“…1 Embora as fraturas dos ossos do antebraço sejam tratadas com sucesso de forma conservadora, os resultados permanecem variáveis e, posteriormente, alguns casos podem exigir manipulação adicional da fratura ou intervenção cirúrgica formal devido a angulações residuais. 2 3 4 5 6 Estudos anteriores mostraram que a falha do tratamento não cirúrgico das fraturas mediodiafisárias em populações pediátricas varia entre 39 e 64%. 3 As alternativas incluem remanipulação fechada e imobilização, pinos e gesso, redução fechada ou miniaberta com haste intramedular (IM) e redução aberta com fixação interna (RAFI) usando placas e parafusos.…”
Section: Introductionunclassified
“…In this method, a nail is placed intramedullary in the centre of the fractured bone and therefore it is a very load-table treatment for bone fractures [39][40][41][42].…”
Section: Intramedullary Nail Osteosynthesismentioning
confidence: 99%
“…Therefore, fractures, which used to be treated nonoperatively previously, are widely treated surgically with bloodless approach these days. 3 …”
mentioning
confidence: 99%
“…Portanto, as fraturas, que costumavam ser tratadas de modo não cirúrgico anteriormente, passaram a ser tratadas cirurgicamente, com abordagem sem sangue, nos dias de hoje. 3 …”
unclassified